Exploration of Employee Knowledge about Financing Products: A Study at Bank Muamalat KC Parepare - Arwin, Arwin; Ulandari, Dewianti; Muhammadun, Muzdalifah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Knowledge of financing products is a crucial factor in providing optimal service to customers, especially in Islamic banking which has special characteristics. Frontliners as the spearhead of service are expected to have adequate understanding of the financing products offered. This study aims to analyze financing products and the level of knowledge of Bank Muamalat KC Parepare employees regarding these products. The approach used is qualitative with a case study design and field research methods. Data were collected through observation, interviews, and documentation, then analyzed using N-Vivo 14 Pro software. The results of the study indicate that Bank Muamalat KC Parepare offers various sharia-based financing products, such as KPR Hijrah, Multiguna, Prohajj Plus, and Back To Back, with sharia contracts such as Murabahah, Musyarakah Mutanaqishah, and Wakalah bi Ujrah. Analysis of employee knowledge levels shows good results, especially in terms of products, contracts, financing, needs, and finance. However, there is still room for further development to improve employee understanding more comprehensively. This study is expected to be a reference for banks in improving employee competence to support excellent service to customers.